(untitled) (CAHIERS MAGELLANES-NS, 2024)
Purpose: The World Health Organization emphasizes the importance of limiting antibiotic treatment in order to reduce antibiotic resistance. The purpose of this systematic review was to look into the relationship between the length of antibiotic treatment and the occurrence of infectious complications after laparoscopic appendectomy. Methods: Following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis, a thorough search was conducted in multiple databases, including PubMed, Scopus, Cochrane Library, Google Scholar, and Web of Science. The search was carried out until May 20, 2023, and eligible studies were found. The duration of antibiotics after laparoscopic appendicectomy in complicated cases was extracted. To determine the complication across different durations of antibiotic use, a meta-analysis was performed. Results: In this systematic review, we searched seven databases and found 1640 articles that were eligible for screening. We included 18 articles in this review after a thorough review. We discovered that the antibiotics used to treat complicated appendicitis vary significantly between institutions. We also discovered that the incidence of complications was nearly the same regardless of antibiotic duration. Conclusion: While the majority of the included studies recommend the use of postoperative antibiotics after a laparoscopic appendectomy, there is no agreement on the optimal duration or specific antibiotic regimen. Notably, all studies found that prolonged antibiotic use following laparoscopic appendectomy for complicated cases did not result in a reduction in infectious complications, such as superficial or deep wound site infections.